Potential neurological applications of Centella asiatica: a brief review - Gofir, Abdul; Wibowo, Samekto; Hakimi, Mohammad (Indonesian Journal of Pharmacology and Therapy, 2021)
Centella asiatica (C. asiatica) or gotu kola has been used traditionally in many Asian countries as herbal medicines for many conditions, such as headache, asthma and memory enhancement. Centella asiatica has been also widely investigated for its neuroprotective effects in animal disease model including epilepsy, Alzheimer’s and Parkinson’s diseases. A brief review of neurological effects studies of C. asiatica in animal model was reported. Eligible studies published through December 2020 from PubMed and EMBASE journal data base were collected. Any keywords related to C. asiatica or gota kola AND neurological conditions were used. The results showed that several experimental studies concerning the neuroprotective properties of C. asiatica have been reported. Phytochemical studies reported that C. asiatica contained many bioactive compounds in which triterpenoids are the most identified. Furthermore, the triterpenoids have proven to have neuroprotective effect due to their effects of anti-inflammatory, antioxidant, improvement of mitochondrial dysfunctions, and increased brain-derived neurotrophic factors. Further studies are needed to investigate the neuroprotective mechanisms of C. asiatica. In conclusion, C. asiatica might have potential as an alternative medicine for neurological conditions, such as stroke, epilepsy, Alzheimer’s and Parkinson’s disease.